Learning From Cervical Cancer Survivors: An Examination of Barriers and Facilitators to Cervical Cancer Screening Among Women in the United States - Virginia Senkomago; April Greek; J. Elizabeth Jackson; Cheryll C. Thomas; Lisa C. Richardson; Vicki B. Benard (SAGE Publishing, 2021)
Background: Screening and timely follow-up have lowered cervical cancer incidence in the US; however, screening coverage, incidence, and death rates have remained fairly stable in recent years. Studies suggest that half of women diagnosed with cervical cancer don't receive appropriate screening prior to diagnosis; cervical cancer survivors can provide crucial insight into barriers and facilitators to screening. Methods: Participants were cervical cancer survivors ≥21 years, identified through population-based central cancer registries (CR) in 3 US states or a social network (SN), Cervivor. CR participants completed a mailed survey on screening history, barriers, and facilitators to screening and sociodemographic data. SN participants completed the same survey online. Results: CR participants (N = 480) were older, with a lower proportion of non-Hispanic white, married, and insured women compared to SN participants (N = 148). Fifty percent of CR and 79% of SN participants were screened 5 years prior to their diagnoses. Of those screened, 28% in both groups reported not following-up on abnormal results. For both groups, the most frequently identified screening barrier was that participants never imagined they would develop cervical cancer (percent agree CR = 76%; SN = 86%), and the facilitator was wanting to take care of their bodies (CR = 95%; SN = 94%). Conclusion: Addressing key barriers to obtaining screening and timely follow-up related to lack of knowledge of cervical cancer risk and screening tests and addressing insurance coverage in the design or modification of interventions may increase cervical cancer screening and lower cervical cancer incidence in the US.